2020
DOI: 10.1108/sef-07-2020-0247
|View full text |Cite
|
Sign up to set email alerts
|

Empirical analysis of dynamic spillovers between exchange rate return, return volatility and investor sentiment

Abstract: Purpose This paper aims to analyze the effects of investors’ sentiment, return and risk series on one to another of selected exchange rates. The empirical analysis consists of a time-varying inter-dependence between the observed variables, with the focus on spillovers between the variables. Design/methodology/approach Monthly data on the index Sentix, exchange rates EUR–USD, EUR–CHF and EUR–JPY are analyzed from February 2003 to December 2019. The applied methodology consists of vector autoregression models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Recently, Aftab et al (2023) showed that economic policy uncertainty significantly increases exchange rate volatility, whereas monetary policy uncertainty in the USA reduces exchange rate risk. Škrinjarić et al (2021) used dynamic models to investigate the effects of investor sentiment, return and risk series on three currency pairs, and Garg and Prabheesh (2021) demonstrated that interest rate differentials have a significant impact on the movements of BRICS exchange rates. Hussain et al (2020) and Hussain and Ben Omrane (2021) showed that return and volatility are sensitive to foreign macroeconomic news announcements, particularly those pertaining to the USA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, Aftab et al (2023) showed that economic policy uncertainty significantly increases exchange rate volatility, whereas monetary policy uncertainty in the USA reduces exchange rate risk. Škrinjarić et al (2021) used dynamic models to investigate the effects of investor sentiment, return and risk series on three currency pairs, and Garg and Prabheesh (2021) demonstrated that interest rate differentials have a significant impact on the movements of BRICS exchange rates. Hussain et al (2020) and Hussain and Ben Omrane (2021) showed that return and volatility are sensitive to foreign macroeconomic news announcements, particularly those pertaining to the USA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To serve as control variables, we collected the following: the European EPU index was collected from [61], the shadow rate for the ECB from [62], and the German VIX from [63]. The EPU index was previously found to be a significant factor in affecting the dynamics of stock markets in Europe and CESEE countries, as seen in [12,[64][65][66][67][68].…”
Section: Data Descriptionmentioning
confidence: 99%
“…Stock market reactions to pandemic news could be classified in the field of behavioral finance, whose roots start in [13][14][15][16][17]. This is due to investors' under-reaction and overreactions to different news, which has a consequence of different stock market movements (of risk and return series) during specific periods [18]. Refs.…”
Section: Introductionmentioning
confidence: 99%